2002
DOI: 10.1126/science.1065543
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of T-bet in T H 1 Lineage Commitment and IFN-γ Production in CD4 and CD8 T Cells

Abstract: T-bet is a member of the T-box family of transcription factors that appears to regulate lineage commitment in CD4 T helper (TH) lymphocytes in part by activating the hallmark TH1 cytokine, interferon-gamma (IFN-gamma). IFN-gamma is also produced by natural killer (NK) cells and most prominently by CD8 cytotoxic T cells, and is vital for the control of microbial pathogens. Although T-bet is expressed in all these cell types, it is required for control of IFN-gamma production in CD4 and NK cells, but not in CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

52
977
9
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,061 publications
(1,040 citation statements)
references
References 28 publications
52
977
9
2
Order By: Relevance
“…The transcription factor t-bet was essential for optimal IFN-+ -production by CD4 + T cells and NK cells, but not by CD8 + T cells [5]. In a study with wild-type and STAT4-deficient DO11.10 TCR-transgenic mice TCR-/anti-CD28-mediated activation of CD4 + , but not of CD8 + T cells, required the STAT4 transcription factor [8].…”
Section: Tyk2 and T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor t-bet was essential for optimal IFN-+ -production by CD4 + T cells and NK cells, but not by CD8 + T cells [5]. In a study with wild-type and STAT4-deficient DO11.10 TCR-transgenic mice TCR-/anti-CD28-mediated activation of CD4 + , but not of CD8 + T cells, required the STAT4 transcription factor [8].…”
Section: Tyk2 and T Cellsmentioning
confidence: 99%
“…Cell transfer and depletion studies, the use of neutralizing antibodies and the availability of gene-deficient mouse strains have helped to define cell types, cytokines, effector mechanisms and transcription factors that contribute to the killing or containment of L. major, the clinical healing of the acute skin lesions, and the long-term control of residual parasites persisting in the tissue. These include NK cells, CD4 + Th1 cells, IFN-+ -producing CD8 + T cells, IL-12, IFN-+ , TNF, inducible nitric oxide synthase (iNOS, NOS2) and NADPH oxidase, signal transducer and activator of transcription 4 (STAT4), interferon regulatory factors (IRF)-1 and 2, and T-bet [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 T-bet belongs to a family of transcription factors, the members of which share a highly conserved DNA-binding domain T-box, flanked by diverse non-DNA-binding domains, which are involved in transactivation or repression. [3][4][5][6] A series of studies in vitro and in vivo showed that T-bet is induced by the T-cell receptor and the IFN-gR/STAT1 signaling pathway in antigen-recognizing naive CD4 þ T cells. The elevated T-bet induces IL-12Rb2 and IFN-g expression, allowing IL-12R/STAT4 signaling to optimize IFN-g expression, and thereby amplifying and establishing the effector commitment of Th1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-g, together with IL-12 and the transcription factors STAT1, STAT4 and T-bet, promotes the development of Th1 cells [2][3]. T-bet (T-box 21) is considered to act as the master transcription factor critically regulating Th1 lineage commitment [3][4][5]. Apart from their protective role in clearing infections, Th1 cells can initiate and maintain chronic inflammatory diseases, e.g.…”
mentioning
confidence: 99%